ТҮРКИЙ ХАЛЫҚЛАРЫНА БЕЛГИЛИ БОЛҒАН ХОЖА НАСРЕДДИН, АЛДАР КӨСЕ, ӨМИРБЕК ЛАҚҚЫҒА БАЙЛАНЫСЛЫ ИЗЕРТЛЕЎЛЕР - Қазахбаев, С.С. (FAN va JAMIYAT, 2025)
The article discusses the emergence and research of legends, tales, and anecdotes about the masters of the word known to the Turkic peoples.